Muscle Cell and Tissue Current Status of Research Field - Sakuma, Kunihiro (IntechOpen, 2018)
In order to complete tissue regeneration, various cells (neuronal, skeletal and smooth) interact coordinately with each other. This book, Muscle Cell and Tissue - Current Status of Research Field, deals with current progress and perspectives in a variety of topics on the skeletal and smooth muscle, stem cells, regeneration, disease or therapeutics. Novel applications for cell and tissue engineering including cell therapy, tissue models and disease pathology modeling are introduced. This book also deals with the differentiation/de-differentiation process of vascular smooth muscle cells in health and disease. Furthermore, natural products to reverse metabolic syndromes are descriptively reviewed. These chapters can be interesting for graduate students, teachers, physicians, executives and researchers in the field of molecular biology and regenerative medicine.